Law on Transparency implementation process, ISO 27001 and Database Reporting on public entities (2016)
During 2015 and 2016, in Pereira (Colombia) a training project addressed to public entities officials was carried out  in areas related with: law on transparency, ISO 27001 and database reporting, though theoretical and practical sessions. As a result, a local researching group developed a set of documents with relevant and updated information on each topic. So, officials can use them as implementation guides in their respective institutions. This paper describes how the training sessions was developed. Finally, the results of the project are presented in a positive way, taking as a reference both an initial scenario and final scenario of greater complexity.